WELD TOE MORPHOLOGY CONSIDERED FATIGUE ASSESSMENT FOR CRUCIFORM JOINTS - WEI GuoQian; LUO YuBing; HUANG FaChao; DANG Zhang; SONG XinLi (Jixie qiangdu)
Considering the morphology of the weld toe,two kinds of FEA models for cruciform joints with arc-shaped weld toe and line-shaped weld toe were established respectively,and their local stress states were analyzed. Regarding the effective notch stress as the governing parameter,the fatigue life of the cruciform joints under cyclic tension load was estimated.Corresponding fatigue test was conduct to validate the estimating results. Research result shows that the morphology of weld toe plays important role on the fatigue performances of welded joints,and arc shape can describe the morphology of weld toe properly. Under cyclic tension load,cracks usually initiate at the weld toe,in detail,at the convex vertex of the weld arc which is near the end of the weld line. Effective notch stress method considering the morphology of weld toes can be utilized for the fatigue assessment of welded structures with satisfying accuracy.